Victorian toadstools and mushrooms - Willis, J. H. (James Hamlyn), 1910-1995 (The Field Naturalists Club of Victoria, 1957)
A key and descriptive notes to 120 different gilled fungi (Family Agaricaceae), with remarks on several other families of the Higher Fungi.